PENGARUH MODEL BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH DALAM PEMBELAJARAN FISIKA SISWA - Norma Sari Hasibuan; Eni Sumanti Nasution; Evitamala Siregar (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2025)
This study aims to determine the effect of Model Based Learning on physics problem-solving abilities of tenth-grade students at SMA Negeri 2 Padangsidimpuan. The research employed a quantitative approach with a quasi-experimental pretest-posttest control group design. The sample consisted of 60 students divided into an experimental class (30 students) and a control class (30 students) selected through purposive sampling. Problem-solving ability data were obtained through validated tests based on Polya indicators, including: understanding the problem, devising a plan, carrying out the plan, and looking back. Data analysis included descriptive statistics, normality tests, homogeneity tests, and independent t-tests. Results showed that the experimental class achieved an average problem-solving ability score of 82.47 (high category), while the control class achieved 68.23 (moderate category). The t-test revealed a significant difference between both groups (t-calculated = 5.872 > t-table = 2.001; p < 0.01). The N-Gain value for the experimental class was 0.71 (high category), while the control class was 0.42 (moderate category). This study confirms that Model Based Learning effectively improves high school students' physics problem-solving abilities